Pengaruh Problem Based Learning Bermuatan SDGs Poin 6 terhadap Kemampuan Pemecahan Masalah Siswa SMP - Zharifah Eka Fitria Nikmah; Purwanti Widhy Hastuti (PT. Komunitas Peneliti Alinea, 2026)
Problem-solving ability is a crucial competency in science learning, as it enables students to analyze, evaluate, and respond to real-world challenges. Integrating the Problem Based Learning (PBL) model with Sustainable Development Goals (SDGs), particularly SDGs Point 6 (Clean Water and Sanitation), provides a meaningful approach to connect scientific concepts with environmental issues such as water pollution. This study aims to: (1) examine the differences in students’ problem-solving abilities between those taught using the PBL model integrated with SDGs Point 6 and those taught using the Discovery Learning model; and (2) determine the effect of the PBL model integrated with SDGs Point 6 on students’ problem-solving abilities. This research employed a quantitative approach with a quasi-experimental design, specifically a Non-equivalent Control Group Design. The study was conducted at SMP Negeri 2 Berbah, involving a population of 128 seventh-grade students. Samples were selected using purposive sampling, with class VII A (32 students) as the experimental group and class VII C (32 students) as the control group. Data were collected using a multiple-choice test instrument to measure problem-solving ability and a non-test instrument in the form of a learning implementation sheet. Data analysis included descriptive statistics, N-gain, independent sample t-test, effect size, and implementation analysis. The results revealed a significant difference in students’ problem-solving abilities between the experimental and control groups (p = 0.000, p < 0.05). Furthermore, the PBL model integrated with SDGs Point 6 had a positive effect on students’ problem-solving abilities, with a Cohen’s d value of 0.46, indicating a medium effect size. These findings suggest that integrating SDGs Point 6 into the PBL model is effective in enhancing students’ problem-solving abilities on water pollution material.